2020
DOI: 10.22541/au.160253847.75056849/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transition Navigator Intervention improves transition readiness to adult care and addresses barriers for youth with Sickle Cell Disease

Abstract: Background Adolescents and young adults (AYA) with Sickle Cell Disease (SCD) experience especially high rates of acute care utilization and increased morbidity, due in part to disease exacerbation and in part to the developmental challenges of adolescence. It is at this very high-risk time that they also face the need to transition their care to adult services, further adding to the heightened morbidity and acute care utilization, if poorly coordinated. Previous research supports the effectiveness of patient n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Of these, four were primarily designed to assess feasibility of web modules, 29 virtual mentoring, 30 genetic education sessions, 31 and online patient portal. 32 Six studies assessed the impact of transition programs on psychosocial outcomes (self-efficacy, disease knowledge, transition readiness), [33][34][35][36][37][38] and one study looked at rate of transfer as a primary outcome. 39 Among the studies designed to test feasibility, four assessed the feasibility of electronic or mobile health-based programs, while the other two programs were conducted in person.…”
Section: Single-arm Pre/post Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, four were primarily designed to assess feasibility of web modules, 29 virtual mentoring, 30 genetic education sessions, 31 and online patient portal. 32 Six studies assessed the impact of transition programs on psychosocial outcomes (self-efficacy, disease knowledge, transition readiness), [33][34][35][36][37][38] and one study looked at rate of transfer as a primary outcome. 39 Among the studies designed to test feasibility, four assessed the feasibility of electronic or mobile health-based programs, while the other two programs were conducted in person.…”
Section: Single-arm Pre/post Studiesmentioning
confidence: 99%
“…Only two studies reported completion rates, making it hard to compare rates of program completion among modalities. Four studies (one web-based and two in person) demonstrated improvements in disease knowledge postintervention, 29,[36][37][38] a program that utilized take-home worksheets demonstrated significant improvements in skill-building, 34 and a 6-month transition navigator program increased transition readiness among participants. 36…”
Section: Single-arm Pre/post Studiesmentioning
confidence: 99%